2021
DOI: 10.1371/journal.pone.0247070
|View full text |Cite
|
Sign up to set email alerts
|

Albumin and the fibrinogen-to-albumin ratio: Biomarkers for the acute phase response following total knee arthroplasty

Abstract: Purpose Complications following total knee arthroplasty (TKA) lead to patient morbidity and cost. While acute phase reactants, such as c-reactive protein (CRP) and fibrinogen, have been used to predict complications following TKA, the extent and duration of changes in albumin levels following TKA are unknown. It is hypothesized that like CRP and fibrinogen, albumin, and the fibrinogen/albumin ratio (FAR) represent useful measures of the acute phase response (APR) following TKA. The purpose of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…After the enrichment analysis, we found that genes have an important role in the acute phase response. It is known that acute phase responses are the body’s response to tissue damage, and acute phase responses may stimulate the initiation of the immune response ( 10 , 11 ). Thus, we analyzed the relationship between the seven genes in THCA and immune infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…After the enrichment analysis, we found that genes have an important role in the acute phase response. It is known that acute phase responses are the body’s response to tissue damage, and acute phase responses may stimulate the initiation of the immune response ( 10 , 11 ). Thus, we analyzed the relationship between the seven genes in THCA and immune infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, fibrinogen is a long-acting plasma acute-phase reactant (33), and the change in albumin level has been Flowchart of this study. A total of 1,216 pregnant women enrolled in our study were selected by inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…attributed to the changes in nutritional status; furthermore, hypoalbuminemia represents a chronic inflammatory state caused by malnutrition (33,34). Likewise, FAR has been proven to be a more powerful inflammatory-based prognostic predictor of overall survival than other single prognostic markers (35)(36)(37); compared with healthy pregnancies, FAR was considered to be an independent risk factor for predicting spontaneous abortion, and increased FAR levels were considered to be related to the thrombotic process in recurrent abortion (38,39).…”
mentioning
confidence: 99%
“…Additionally, FAR is a predictor of diabetic kidney disease with better performance than fibrinogen and albumin alone [55]. It also reflects the activity of ANCAassociated vasculitis [56], or the acute-phase response after total knee arthroplasty [57]. Similarly, BAR was shown to be a predictor of long-term mortality in patients with acute myocardial infarction in the intensive care unit [58], as well as hospital mortality in older adults [59] or patients with acute pulmonary thromboembolism [60].…”
Section: Discussionmentioning
confidence: 99%